2023
DOI: 10.1039/d2py01377k
|View full text |Cite
|
Sign up to set email alerts
|

A facile method based on a superabsorbent polymer composite for concentration and separation of exosomes from cell culture media

Abstract: Superabsorbent polymers of alginate and poly(acrylamide-co-acrylic acid) composite are used to construct a facile, equipment-free and highly efficient method for concentration and separation of exosomes from cell culture medium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recently, Li et al 170 reported that the hollow morphologies of HCPs could diminish mass transfer resistance and enhance active site exposure. N,N′-Bis(salicylidene)-ethylenediamine (Salen) and fluoranthene could be used as the monomer to generate hollow spherical HCPs by using the SiO 2 template method; after loading with CO 2+ , the resulting HCPSS-FS-4-80-Co exhibited exceptional performance, achieving a remarkable 94% CO 2 conversion yield, surpassing its bulk counterpart by a significant 52%.…”
Section: Co 2 Conversionmentioning
confidence: 99%
“…Recently, Li et al 170 reported that the hollow morphologies of HCPs could diminish mass transfer resistance and enhance active site exposure. N,N′-Bis(salicylidene)-ethylenediamine (Salen) and fluoranthene could be used as the monomer to generate hollow spherical HCPs by using the SiO 2 template method; after loading with CO 2+ , the resulting HCPSS-FS-4-80-Co exhibited exceptional performance, achieving a remarkable 94% CO 2 conversion yield, surpassing its bulk counterpart by a significant 52%.…”
Section: Co 2 Conversionmentioning
confidence: 99%
“…The aggregate method is commonly employed for exosome extraction from lactic acid bacteria, which leverages the interaction force between aggregates and polysaccharides or proteins to isolate exosomes. Aggregating agents such as PEG ( Weng et al, 2016 ) or polyacrylamide (PAA) ( Li et al, 2023b ) can be used to separate exosomes. PEG6000 is typically employed due to its optimal separation efficiency, as molecular weight greater than 6,000 diminishes its effectiveness.…”
Section: Isolation and Purification Of Lactobacilli Exosomes: Methods...mentioning
confidence: 99%